Expert System Application to Diagnose Degenerative Diseases Using Methods Certainty Factor - Dwi Imansyah; Dewi Suranti; Eko Suryana (Penerbit Jurnal Indonesia, 2024)
Degenerative diseases are diseases that cause damage or destruction to body tissue or organs that arise due to a decrease in the function of one or more of the body's organs which are very susceptible to elderly people. Considering the large negative impact of degenerative diseases, it is necessary to prevent or seriously treat the dangers of degenerative complications. Efforts to minimize this danger can be made by increasing public awareness about things that can cause degenerative diseases. Therefore, we need a system that can help as an alternative to consulting a doctor for the general public. Therefore, this expert system was built using the Certainty Factor method which can be used as a solution in using an expert system to diagnose this Degenerative disease. In its application, the certainty factor method can provide a percentage level of confidence in a disease, if the user has or selects symptoms so that they can determine the type of disease they are suffering from. Based on the tests carried out, it can be concluded that this expert system application can be used by users to make an early diagnosis of degenerative diseases. This expert system can be accessed at the link www.sp_ Degenerative.com. Making it easier for users to consult.